Analytical Solutions of Water Inflow for Foundation Pit in Confined Water Stratum - Jingjing Shen; Yue Jiang; Jie Wu; Pengfei Li (Applied Sciences, 2023)
This paper is aimed at the problem of inaccurate calculation of the water inflow of a foundation pit with a suspended water-proof curtain in a confined water stratum. According to the groundwater hydraulics principle, the theoretical model of the seepage field of the foundation pit is established, and the analytical formula of the water inflow for the circular, strip, and rectangular foundation pits is deduced. The seepage path influence coefficient α related to the water-proof curtain insertion ratio, the thickness of the confined aquifer, and the radius of the foundation pit is proposed and obtained by the positive and negative analysis of numerical simulation. The coefficient is used to correct the equivalent seepage length in the pit and directly affect the calculation result of water inflow. Finally, based on the calculation results of the analytical solution of water inflow, the relationship between the scale of the foundation pit and the water control effect is discussed. The research results show that the theoretical analysis results in this paper are in good agreement with the numerical results and the measured data in the field: when the size of the foundation pit is too large, it is not suitable to use the suspended water-proof curtain as the water control measure.